New Evidence on Fiscal Adjustment and Growth in Transition Economies - Gupta, Sanjeev; Segura-Ubiergo, Alex.; Simone, Alejandro (Washington, D.C. : International Monetary Fund, 2006)
This paper analyzes the relationship between fiscal adjustment and real GDP growth in a panel of 26 transition economies during 1992-2001. Unlike most previous studies using cross-country regressions, the paper finds a positive and statistically significant relationship between fiscal adjustment and growth that is robust to different model specifications and estimation methods. The paper also presents country experiences to delve deeper into the mechanisms that may underlie this statistical relationship.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet